Pengaruh kepemimpinan dan Motivasi Kerja Pegawai Terhadap Kedisiplinan Guru di Madrasah Aliyah Negeri - Susanti, Fitri; Zakariyah, Zakariyah; Komalasari, Mala; Warlizasusi, Jumira (Kharisma: Jurnal Administrasi dan Manajemen Pendidikan, 2023)
The purpose of conducting research is to test 1) whether leadership influences teacher discipline at MAN 1 Kepahiang. 2) Does work motivation affect teacher discipline at MAN 1 Kepahiang? 3) whether the variables of leadership and motivation affect teachers' work discipline. This research uses quantitative methods. The population in this research consisted of 40 teachers at MAN 1 Kepahiang, where the sampling used the total sampling technique. Data collection was carried out using questionnaires and documentation. This study uses an explanatory research approach, which is a type of research that seeks to explain the influence of variables through hypothesis testing. The independent variable is X1 = leadership, X2 = teacher's work motivation, and the dependent variable is work discipline (Y). Furthermore, the data were analyzed quantitatively using a statistical model in a computer program (SPSS 22.0), with descriptive analysis techniques and multiple linear regression analysis. The conclusions drawn by the researchers are 1) leadership affects the work discipline of teachers at MAN 1 Kepahiang, 2) work motivation has an influence on the work discipline of teachers at MAN 1 Kepahiang, 3) Leadership and work motivation jointly affect the work discipline of teachers at MAN 1 Kepahiang. So to improve teacher work discipline, a leader must apply leadership that can uphold work discipline; besides that, work motivation must also be well developed because good work motivation can increase work discipline, which will increase work results and achieve organizational goals.